Modeling euro area bond yields using a time-varying factor model - Tomáš Adam; Marco Lo Duca (European Central Bank (ECB), 2017)
In this paper, we study the dynamics and drivers of sovereign bond yields in euro area countries using a factor model with time-varying loading coefficients and stochastic volatility, which allows for capturing changes in the pricing mechanism of bond yields. Our key contribution is exploring both the global and the local dimensions of bond yield determinants in individual euro area countries using a time-varying model. Using the reduced form results, we show decoupling of periphery euro area bond yields from the core countries yields following the financial crisis and the scope of their subsequent re-integration. In addition, by means of the structural analysis based on identification via sign restrictions, we present time varying impulse responses of bond yields to EA and US monetary policy shocks and to confidence shocks.
Keywords: C11; G01; E58; 330; bayesian estimation; bond yield; factor model; sovereign debt crisis; stochastic volatility